2020
DOI: 10.12659/ajcr.921241
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroid Injection-Induced Pancreatitis: A Case Report

Abstract: Rare co-existance of disease or pathology Background:Degenerative disc disease of the lumbar spine can be associated with spinal canal and neuroforaminal stenosis, resulting in severe pain. Conservative approaches to treatment are generally recommended initially, especially in the elderly. Epidural corticosteroid injections can provide significant but temporary pain relief and are a commonly performed procedure in pain management. Pancreatitis caused by corticosteroids is unusual and the prognosis typically is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Intra-articular steroid injections as a cause has only been reported once before in a Letter to the Editor [4]. There is one report of a case of pancreatitis due to a lumbar epidural steroid injection [7]. Our patient had been on long-term topical fluticasone and budesonide for EoE without any episodes of pancreatitis, so this is not likely the etiology.It is interesting that our patient received a triamcinolone injection in the past, which has been shown to have more of a systemic effect, but did not develop pancreatitis.…”
Section: Discussionmentioning
confidence: 69%
“…Intra-articular steroid injections as a cause has only been reported once before in a Letter to the Editor [4]. There is one report of a case of pancreatitis due to a lumbar epidural steroid injection [7]. Our patient had been on long-term topical fluticasone and budesonide for EoE without any episodes of pancreatitis, so this is not likely the etiology.It is interesting that our patient received a triamcinolone injection in the past, which has been shown to have more of a systemic effect, but did not develop pancreatitis.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have reported that GCs can lead to acute pancreatitis [ 12 14 ]. China’s latest guidelines [ 15 ] suggest that the diagnosis of acute pancreatitis should meet at least two of the following three criteria: (1) acute, sudden, persistent, severe upper abdominal pain, which may radiate to the back; (2) serum amylase and/or lipase activities at least three times higher than the upper limit of normal levels; (3) enhanced CT/MRI showing typical AP imaging changes (pancreatic edema or peripancreatic effusion).…”
Section: Discussionmentioning
confidence: 99%
“…A thorough review of the patients’ medications is important in all cases of acute pancreatitis. A clear history of recent steroid use, in the absence of other causes of acute pancreatitis, warrants immediate cessation of steroids to prevent further pancreatic damage [ 8 ].…”
Section: Discussionmentioning
confidence: 99%